Analysis of Merchandise Inventory Management at Petra Women's Cooperative (Case Study of Coop Mart Plaju) - Sri Hartati; Neti Rohiya (PT FORMOSA CENDEKIA GLOBAL, 2023)
Merchandise inventory plays an important role in the process of buying and selling at trading companies, so it is important for companies to manage and monitor their inventory. The problem discussed in this study was the lack of management of merchandise inventory which often resulted in the shortage of stock. This research was conducted at Petra Women's Cooperative (Coop Mart) located at Jl. Antara Annex II No. 292 Plaju Palembang. The data used in this study were primary and secondary data. The method applied in the research was qualitative and quantitative analysis method. The results of this analysis showed that the management of merchandise inventory of Petra Women's Cooperative (Coop Mart) was not regularly carried out as seen from the calculation of inventory turnover, safety stock and reorder point which fluctuated. This was caused by the lack of control over the goods entry and exit, which would affect inventory. Therefore, inventory management analysis was very essential to do to prevent shortages of goods.